If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 8x + 20 + -1x = 0 Reorder the terms: 6 + 20 + 8x + -1x = 0 Combine like terms: 6 + 20 = 26 26 + 8x + -1x = 0 Combine like terms: 8x + -1x = 7x 26 + 7x = 0 Solving 26 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 7x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 7x = 0 + -26 7x = 0 + -26 Combine like terms: 0 + -26 = -26 7x = -26 Divide each side by '7'. x = -3.714285714 Simplifying x = -3.714285714
| -x^2+14x=38 | | 7(x+9)-9=110 | | 2x+44=180 | | 9m-6m-2m=20 | | x/7=32/56 | | 5x+656789=0 | | 3x+5x=-7x | | 5x+4=5x+7 | | 5a+15+19= | | -3+12x-2=19 | | 94=d-77 | | B/56=2 | | 78=3j | | 64-x=7x | | 9b^2-36= | | 3-8k-20=71 | | 4x+4(2x+9)=12x+36 | | 25=19+c | | g=(5x-3)(2x+1) | | 11g+g+g+3g-15g=19 | | 63=d-18 | | U=y(a+b) | | 7t-15t-2t+16t=-8 | | 7q+5q-7q=20 | | 13x-yx=17 | | a-a+4a-a=15 | | 12n+3n-9n-5n=20 | | -27w=-648 | | 2x^2-18x-364=0 | | 12u=552 | | 4s-2s-s=18 | | 4m-2m-m=12 |